Facile (3+2) Cycloaddition between an N-Heterocyclic Olefin and Nitrous Oxide at Ambient Conditions - Ariai, Jama; Becker, Jonathan; Gellrich, Urs; Justus Liebig University Giessen (My University, 2024)
We report that a gem-dimethylated N-heterocyclic olefin (NHO) reacts with N2O at ambient pressure and room temperature to give an imidazolone and an azine formed from intermediately generated 2-diazopropane. The in situ formation of transient diazopropane was indirectly proven by its engagement in a facile cycloaddition with norbornene. According to our studies, the reaction sequence consists of a rate-determining (3+2) cycloaddition between the NHO and N2O, followed by a cycloreversion that releases the diazoalkane. This mechanistic proposal is supported by DFT calculations. Eyring analysis using temperature-variable 1H NMR spectroscopy allowed us to determine the activation parameters of the initial (3+2) cycloaddition (Δ≠H=11.2(4) kcal/mol, Δ≠S=−39.8(13) e.u., 293–308 K). Frontier molecular orbital analysis shows that the polarization of the π-bond of the NHO decisively facilitates the cycloaddition.
Keywords: ddc:540